(untitled) (Journal of Environmental Microbiology and Toxicology, 2019)
The inappropriate removal, manufacturing and prospecting actions and unnecessary use of agricultural chemical compounds have triggered an international issue. Eliminating these kinds of contaminants by means of bioremediation is a less expensive approach in the long term notably at low concentrations, in which various other approaches for instance physical or chemical approaches is probably not useful. In this work we screen the ability of a molybdenum-reducing bacterium isolated from polluted soil to make use of pesticides as electron donor sources for assisting reduction and as carbon sources for growth. The bacterium was not able to use pesticides as electron donors, nonetheless, the bacterium can grow on coumaphos separate from molybdenum reduction. Optimum conditions for Mo-blue production were at pH 6.3 and between 25 and 37 oC, glucose as electron donor, phosphate at 5.0 mM and sodium molybdate between 15 and 20 mM. Reduction was inhibited by Hg, Ag and Cr at 2 ppm by 91.9, 82.7 and 17.4 %, respectively. Biochemical analysis tentatively and partially identified the bacterium as Bacillus sp. strain Neni-12. This is a novel Mo-reducing bacterium with coumaphos degrading capability.